2021
DOI: 10.3389/fimmu.2021.719115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening for TLR7 Variants in Young and Previously Healthy Men With Severe COVID-19

Abstract: IntroductionLoss-of-function TLR7 variants have been recently reported in a small number of males to underlie strong predisposition to severe COVID-19. We aimed to determine the presence of these rare variants in young men with severe COVID-19.MethodsWe prospectively studied males between 18 and 50 years-old without predisposing comorbidities that required at least high-flow nasal oxygen to treat COVID-19. The coding region of TLR7 was sequenced to assess the presence of potentially deleterious variants.Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 27 publications
5
94
0
2
Order By: Relevance
“…It is noteworthy the discovery of two rare and deleterious germinal variants of the TLR7 gene in two couples of young male siblings with no reported comorbidities and displaying a severe COVID-19 phenotype: the frameshift variant with maternal segregation c.2129_2132del, p.Gln710Argfs*18 and the missense variant c.2383G > T, p.Val795Phe (Table 1) [42]. The alteration of the response to type I and type II IFN subsequent to imiquimod administration, a TLR7 receptor agonist, confirmed the importance of the maintenance of TLR pathway in COVID-19 pathogenesis [42,43]. These results found confirmation in a recent independent cohort study performed in Italy, which highlighted the presence of deleterious variants of TLR7 in 2.1% of severely affected males in comparison with asymptomatic individuals [44].…”
Section: Discussionmentioning
confidence: 71%
“…It is noteworthy the discovery of two rare and deleterious germinal variants of the TLR7 gene in two couples of young male siblings with no reported comorbidities and displaying a severe COVID-19 phenotype: the frameshift variant with maternal segregation c.2129_2132del, p.Gln710Argfs*18 and the missense variant c.2383G > T, p.Val795Phe (Table 1) [42]. The alteration of the response to type I and type II IFN subsequent to imiquimod administration, a TLR7 receptor agonist, confirmed the importance of the maintenance of TLR pathway in COVID-19 pathogenesis [42,43]. These results found confirmation in a recent independent cohort study performed in Italy, which highlighted the presence of deleterious variants of TLR7 in 2.1% of severely affected males in comparison with asymptomatic individuals [44].…”
Section: Discussionmentioning
confidence: 71%
“…The specific effector gene in this region has recently been narrowed down to LZTFL1 , a gene with uneven distribution amongst different geographical populations, and it has been suggested that this locus could be investigated as a therapeutic target [ 8 ]. Furthermore, there is growing evidence that rare X chromosomally-located variants of TLR7 are associated with severe COVID-19 response in young men [ 13 , 14 ], and potentially constitute clinically relevant screening targets [ 15 ].…”
Section: The Role Of Host Genetics In Covid-19 Infectionsmentioning
confidence: 99%
“…Loss of function was confirmed when experiments with primary PBMCs showed no upregulation of TLR7 and a failure to induce IFN-inducible genes (ISGs) after stimulation with a TLR7 agonist ( 10 ). Later, more such cases of deleterious TLR7 variants in severe male patients have been described ( 11 , 26 , 27 ), suggesting that a loss-of-function of TLR7 could explain some cases of severe COVID-19 which result in functional defects of type 1 IFN. Likewise, single nucleotide polymorphisms (SNPs) could alter TLR7’s effectivity.…”
Section: Subsectionsmentioning
confidence: 99%
“…Since TLR7 is located on the X chromosome, mutations in TLR7 will affect males more than females, who bear two X chromosomes per cell. TLR7 deficiency has been reported as a genetic mediator for severe COVID-19 especially in younger males, with percentages of 1-2% found across cohorts ( 10 , 11 , 26 , 27 ). Therefore, genetic screening for TLR7 primary immunodeficiency was recommended in young males with severe COVID-19 in the absence of other relevant risk factors ( 11 , 26 , 27 ).…”
Section: Subsectionsmentioning
confidence: 99%
See 1 more Smart Citation